Fare ricerca di campo tra i Maxakali: Riflessioni sulla pratica etnografica nella complessità di un mondo indigeno amerindio - Magnani, Claudia (Antropologia Pubblica, 2024)
Nowadays, the worlds of lowlands’ indigenous people are dynamic and complex. Traditional and modern practices, cosmological and pragmatic elements, cross each other in an original way, redefining their particular realities in a historical contingency characterized by wider political and social implications. Doing ethnography among the Maxakali, an indigenous people from the North East of Minas Gerais State in Brazil, involves confronting a lot of roles, positions, boundaries and epistemological and ethical problems, that show us the dilemmas of the ethnographic practice and of the anthropological discourse. Still engaged in a fieldwork experience with a Maxakali community, I´ll try to shed light on some of the complex dimensions – human, epistemological, political – that are involved in doing ethnography and producing knowledge about the other. Through a critical and reflexive analyses of the self presence in the fieldwork, the ethnography is investigated as an inter-subjective and sensible social practice – as well as the practices observed by the ethnographer – that occurs in a field of historical and epistemological asymmetries. A reflexion about the personal, social and political conjectures of the research finally claims for a more explicit commitment of the anthropologist, as an intellectual and political ally of the co-participant of his fieldwork.